2013
DOI: 10.1007/s00264-013-2135-7
|View full text |Cite
|
Sign up to set email alerts
|

A cementless hip system with a new surface for osseous integration

Abstract: Although the incidence of radiolucent lines was decreased, the revision rate was considerably increased compared to other uncemented hip implants with grit-blasted surfaces in the short- to mid-term follow-up of our study. Subsequent studies are needed to confirm whether these changes in implant material and surface affect the radiological and clinical outcome in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This illustrates that initial metal-bone contact, while sometimes invisible on the radiograph, exists in both cup designs. This is corroborated by the good long-term and short-term clinical successes of the 2D and 3D cup designs respectively [10] , [11] , [12] , [13] , [16] , [17] , [24] , [25] , [31] .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This illustrates that initial metal-bone contact, while sometimes invisible on the radiograph, exists in both cup designs. This is corroborated by the good long-term and short-term clinical successes of the 2D and 3D cup designs respectively [10] , [11] , [12] , [13] , [16] , [17] , [24] , [25] , [31] .…”
Section: Discussionmentioning
confidence: 78%
“…Porous coated uncemented acetabular components are commonly used in total hip arthroplasty with good long-term survival [9] , [10] , [11] , [12] , [13] , [16] , [17] , [25] . Conversely, retrieval studies have shown that bone fixation occurs on a relatively small percentage of the available porous surface and fibrous growth is commonly present on many acetabular implants with porous surfaces [9] , [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total hip replacement is considered by many to be the most important operation developed in the 20th century in terms of relieving the amount of human suffering . Increased efforts were made to improve osseointegration of these implants by modification of their surface properties . Today, hydroxyapatite coatings of titanium stems are successfully used in hip arthroplasty like the Corail ® hip system (Depuy Co., Warsaw, IN) .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Increased efforts were made to improve osseointegration of these implants by modification of their surface properties. [9][10][11] Today, hydroxyapatite coatings of titanium stems are successfully used in hip arthroplasty like the Corail V R hip system (Depuy Co., Warsaw, IN). 12 In recent research, these surfaces were further modified to release rhBMP-2 and found to significantly alter bone volume close to the interface.…”
Section: Introductionmentioning
confidence: 99%